Internal Labor Markets and Firm Innovation - Lee, Jeong-Yeon; 강성춘 (Seoul Journal of Business, 2017)
This study examines the relations between internal labor markets and organizational innovation. From the knowledge-based view, we hypothesize that ILMs will be positively associated with organizational innovation by encouraging employees to share and integrate their knowledge. We also attempt to uncover potential moderating effects of environmental dynamism by focusing on its influence on knowledge stock and flow under ILMs. The empirical results from a sample of 205 firms show that ILMs have an overall positive influence on organizational innovation. However, the positive effect is more pronounced as environmental dynamism increases.